A randomized clinical trial to evaluate the efficacy of L-carnitine L-tartrate to modulate the effects of SARS-CoV-2 infection - Badaro, Roberto; Barbosa, Josiane Dantas Viana; de Araujo Neto, Cesar Augusto; Machado, Bruna Aparecida Souza; Soares, Milena Botelho Pereira; de Senna, Valter; Taddeo, Marcelo; de Araújo, Lila Teixeira; Durkee, Shane; Donninger, Raymond; Judge, Kevin; Saiyed, Zainulabedin (Frontiers in Nutrition, 2023)
L-carnitine (LC) has been associated with inflammatory mediator reduction and with down-regulating the angiotensin-converting enzyme-2 (ACE2) receptor, which is the target of SARS-CoV-2 attachment. This pilot phase 2 randomized, double-blind placebo-controlled trial contained 2 cohorts. Cohort 1 comprised 101 individuals with negative RT-PCR SARS-CoV-2 test results who cohabitated with an individual diagnosed with SARS-CoV-2 infection. Cohort 2 comprised 122 individuals with positive SARS-CoV-2 RT-PCR test results who were asymptomatic or had mild COVID-19 pneumonia symptoms. Participants in each cohort were randomized 1:1 to receive either 2g elemental oral LC supplementation or placebo daily for 21 days. Primary endpoints included adverse events, SARS-CoV-2 infection incidence in Cohort 1, and disease progressions in Cohort 2. Secondary endpoints included between-group laboratory profile comparisons and Cohort 2 ACE1/ACE2 plasma levels. Disease progression was compared between the Cohort 2 groups using chest computed tomography. In Cohort 1, two SARS-CoV-2 infections occurred in each group. The common adverse events included headache, dyspnea, and tiredness. In Cohort 2, platelet counts were elevated, and fibrinogen levels reduced in the LC group compared with those of the placebo group. Our study showed that LC was well-tolerated and suggests it modulates coagulation pathways. Furthermore, chest computed tomography images of the Cohort 2 LC group showed significant lung lesion improvement, suggesting that LC may slow COVID-19 progression.